Antitumor Activity of Intratumoral Ethanol Injection in an Orthotopic Pancreatic Cancer Cell Mouse Xenograft Model - Wen-Ying Zhang; Zhen-Dong Jin; Feng Liu; Hai-Hua Yuan; Bin Jiang (Gastroenterology Research and Practice)
Purpose. Pancreatic cancer is a lethal disease and usually is diagnosed at advanced stages of disease. This study assessed the effects of intratumoral ethanol injection using an endoscopic ultrasound (EUS) probe on the control of pancreatic cancer in a mouse orthotopic xenograft model. Materials and Methods. The subcutaneous and orthotopic human pancreatic cancer cell mouse xenograft models were established. Different concentrations of ethanol (0–95%) were injected into subcutaneous xenograft tumors. In the orthotopic tumor model, ethanol was injected into the tumor lesions under the guidance of a high-frequency EUS probe. Tumor volume, relative tumor volume (RTV), and histopathology were evaluated. The serum amylase level was analyzed at baseline and 24 h after treatment in the orthotopic tumor model. Results. Injection of 40–95% ethanol induced tumor necrosis in the subcutaneous tumor model, while there was no statistical difference between the RTVs of the two groups (P=0.81). In the orthotopic tumor model, the RTV of the 80% ethanol treatment group was less than that of the saline injection group (P<0.01); and histologically, there was a large area of necrosis observed in the 80% ethanol group. The serum amylase level was slightly elevated at 24 h after injection and returned to the baseline level at 7 days. Conclusion. Injection of 80% ethanol into xenograft tumor lesions of orthotopic pancreatic cancer resulted in tumor necrosis, and the procedure was safe and effective. Future studies will further confirm its antitumor activity as well as assess its safety and feasibility.